Peran Media Digital dalam Manajemen Lembaga Filantropi di Era Generasi Z - Deva Arta Nola; Erla Deliyana; Hasrin Putri Arti; Naufal Agistya Falih; Salwaa Mumtazah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research aims to analyze the role of Generation Z in developing the digital economy in Indonesia, with a focus on the phenomenon of successful young entrepreneurs at a young age through the utilization of technology and digital marketing strategies. One of the real examples is a 16-year-old teenager who managed to achieve a turnover of five billion rupiah in 1.5 years through a hard selling strategy of imported hair accessories products on the e-commerce platform. The research method used is qualitative descriptive with a case study approach. The research results show that the success of the young entrepreneur is supported by the utilization of digital marketing strategies, creativity in product branding, and the ability to read market trends quickly. This finding reinforces the view that Generation Z has great potential as a driver of the national digital economy in the future.